2019
DOI: 10.1159/000500658
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating Sensorineural Hearing Loss

Abstract: Background: Several otologic conditions can present with fluctuating sensorineural hearing loss, including Ménière’s disease, autoimmune inner ear disease, and enlarged vestibular aqueduct. Although these 3 etiologies vary greatly, distinguishing between these conditions at initial presentation can be challenging. Furthermore, initial treatment of these conditions is often similar. In this review, we discuss historical and current perspectives on diagnosis and treatment of these conditions. Summary: A literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…One proposed mechanism is that intracranial pressure changes results in inner ear pressure changes by a widened vestibular aqueduct [ 26 , 27 ]. Like Ménière’s disease, periodic microruptures in the already distended endolymphatic membranes leads to disturbances in ion concentration in the endolymphatic and perilymphatic spaces, loss of the membrane potential, and resultant alterations in hearing and vestibular function [ 26 , 28 ]. Due to the altered fluid flow of the inner ear system, worsening hearing thresholds have been associated with head trauma, strenuous exercise, and upper respiratory infections [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One proposed mechanism is that intracranial pressure changes results in inner ear pressure changes by a widened vestibular aqueduct [ 26 , 27 ]. Like Ménière’s disease, periodic microruptures in the already distended endolymphatic membranes leads to disturbances in ion concentration in the endolymphatic and perilymphatic spaces, loss of the membrane potential, and resultant alterations in hearing and vestibular function [ 26 , 28 ]. Due to the altered fluid flow of the inner ear system, worsening hearing thresholds have been associated with head trauma, strenuous exercise, and upper respiratory infections [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Like Ménière’s disease, periodic microruptures in the already distended endolymphatic membranes leads to disturbances in ion concentration in the endolymphatic and perilymphatic spaces, loss of the membrane potential, and resultant alterations in hearing and vestibular function [ 26 , 28 ]. Due to the altered fluid flow of the inner ear system, worsening hearing thresholds have been associated with head trauma, strenuous exercise, and upper respiratory infections [ 28 ]. A recent meta-analysis revealed that decreased hearing after minor head trauma was reported in one-third of patients with EVA [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common sensory disorder is hearing loss, affecting around 15% of the population [4]. Sensorineural hearing loss (SNHL) and vestibular disorders are caused by Disclaimer/Publisher's Note: The statements, opinions, and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s).…”
Section: Introductionmentioning
confidence: 99%
“…Sensorineural hearing loss (SNHL) is one of the most common clinical diseases of ophthalmology and otorhinolaryngology, which is the abnormality of the auditory system to feel and process the sound resulted from various factors [ 1 ]. With the acceleration of population aging, hearing loss is the third chronic disease affecting the healthy life of the elderly [ 2 ] and the incidence of SNHL is still on the rise [ 3 ]. The main effect of adult hearing loss is communication obstruction, even psychological disorders.…”
Section: Introductionmentioning
confidence: 99%